OPTIMALISASI PENGELOLAAN BUMDES MELALUI PENERAPAN MANAJEMEN MODERN DAN INOVASI BERKELANJUTAN DALAM MENGEMBANGKAN EKONOMI DESA - Se, Hyronimus; Fatima, lmaculata; Rodja, Mohamad Choiry (LPPM Universitas Flores, 2025)
This research examined optimising the management of Village-Owned Enterprises (BUMDes) through modern management practices and sustainable innovation in developing the rural economy in Watusipi Village, North Ende District, Ende Regency. The activity was carried out as community service. It was attended by 43 participants, consisting of lecturers, students, village government representatives, BUMDes managers, and village communities, including community leaders, youth, and women members of village business groups. The findings of this study highlight the importance of collaborative efforts between village governments, BUMDes managers, and communities in achieving sustainable development goals. Integrating technology and innovative business practices will revive its business, including savings and loans, payment services, and virgin coconut oil management, which has not been running optimally. The study results show a need for significant restructuring of BUMDes through its adaptability in modern BUMDes operations to effectively contribute to improving the welfare of the village community and the economic resilience of Watusipi village.